The Influence of Education Level On The Behavior of Voter in Pante Ceureumen District, West Aceh Regency in The 2024 Legislative Elections - Reza Sumita Dewi; Annisah Putri; Riki Yulianda; Reza Fahlevi (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2025)
This study aims to analyze the effect of education level on voter behavior in Pante Ceureumen District, West Aceh Regency, in the 2024 Legislative Election. Voter behavior is an important factor in determining election results and is influenced by various aspects, one of which is the level of education. The theory in this study is the theory of voter behavior using three approaches, namely the Sociological Approach, Psychological Approach, and rational choice. This research uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to voters in Pante Ceureumen District. The population in the study were people who had the right to vote in the 2024 legislative elections in the pante ceureumen sub-district, which amounted to 8,444 people who were then sampled using the slovin formula with a 5% margin of error, then the results obtained were 382 samples, then the data obtained and analyzed using simple linear regression to determine the effect of education level variables on voter behavior. Based on the Hypothesis Test, the tcount value of the education level is 11.622 with a significance of 0.000. Judging from the tcount value of 11.622> t table 1.960 and a significance value of 0.000 <0.05. So the results showed that there was a significant influence between the level of education and voter behavior in Pante Ceureumen District.